Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board Part XVI. Chemical Pulps and Writing and Printing Papers from Wattle Woods (Acacia decurrens, Willd. and Acacia mollissima, Willd.) - Bhat, R. V.; Virmani, K. C. (Indian Forester, 1953)
Laboratory experiments on the production of chemical pulps by the sulphate process from wattle woods (Acacia decurrens and Acacia mollissima, Willd.) are described. Results of five pilot plant experiments on the production of chemical pulps and writing and printing papers are also included. In the case of three pilot plant experiments, a mixture of equal quantities of the two species of wattle wood was used for the digestion. These wattle woods are short-fibred and, hence, admixture of their pulps with about 40% of a long-fibred pulp such as bamboo pulp is necessary for making paper. Papers made from mixtures of wattle and bamboo pulps prepared under suitable conditions had good formation and satisfactory strength properties. Three samples of papers are appended. One sample is from A. decurrens, another from A. mollissima and the third from a mixture of the woods of the two species.